Efeito protetor do extrato hidroalcoólico de própolis marrom nas lesões vaginais induzidas pelo herpes simples vírus tipo 2 - Sartori, Gláubia da Silva (2013)
Propolis is a natural compound and has been highlighted for its antioxidant, antiinflammatory and antiviral properties. The purpose of this study was to investigate if brown hydroalcoholic propolis extract (HPE) protects against vaginal lesions caused by herpes simplex virus type 2 (HSV-2) in female BALB/c mice. The treatment was divided in 5 days of pre-treatment with HPE [50 mg/kg, once a day, intragastric (i.g.)], HSV-2 infection [10 ml of a solution 1x102 plaque-forming unit (PFU/ml 1 HSV-2), intravaginal inoculation at day 6] and post-treatment with HPE (50 mg/kg) for 5 days more. At day 11, in vivo (score of lesions) and ex vivo analysis [haematological and histological evaluation; superoxide dismutase (SOD), catalase (CAT) and myeloperoxidase (MPO) activities; reactive species (RS), tyrosine nitration, non-protein thiols (NPSH) and ascorbic acid (AA) levels] were carried out. HPE treatment reduced extravaginal lesions and the histological damage caused by HSV-2 infection in vaginal tissues of animals. HPE was able to decrease RS, tyrosine nitration, AA levels and MPO activity. Also, it protected against the inhibition of CAT activity in vaginal tissues of mice. HPE promoted protective effect on HSV-2 infected animals by acting on inflammatory and oxidative processes, and this effect probably is due its antioxidant and anti-inflammatory properties.